2014
DOI: 10.1021/bi500532e
|View full text |Cite
|
Sign up to set email alerts
|

Human Frataxin Activates Fe–S Cluster Biosynthesis by Facilitating Sulfur Transfer Chemistry

Abstract: Iron–sulfur clusters are ubiquitous protein cofactors with critical cellular functions. The mitochondrial Fe–S assembly complex, which consists of the cysteine desulfurase NFS1 and its accessory protein (ISD11), the Fe–S assembly protein (ISCU2), and frataxin (FXN), converts substrates l-cysteine, ferrous iron, and electrons into Fe–S clusters. The physiological function of FXN has received a tremendous amount of attention since the discovery that its loss is directly linked to the neurodegenerative disease Fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
145
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(156 citation statements)
references
References 46 publications
6
145
1
Order By: Relevance
“…We thus conclude that FXN is not required for persulfide formation of NFS1 as confirmed by mass spectrometry analysis. These results challenge two recent studies reporting a stimulatory effect of FXN and its yeast homologue, Yfh1, on NFS1 persulfide formation 12,31 . In these studies, the formation of persulfide was monitored using 35 S labelling of L-cysteine.…”
Section: Discussioncontrasting
confidence: 90%
See 2 more Smart Citations
“…We thus conclude that FXN is not required for persulfide formation of NFS1 as confirmed by mass spectrometry analysis. These results challenge two recent studies reporting a stimulatory effect of FXN and its yeast homologue, Yfh1, on NFS1 persulfide formation 12,31 . In these studies, the formation of persulfide was monitored using 35 S labelling of L-cysteine.…”
Section: Discussioncontrasting
confidence: 90%
“…These results rule out the hypothesis that FXN stimulates sulfide release by enhancing persulfide formation on NFS1, as proposed by others 11,12,14,31 . FXN has also been proposed to stimulate iron entry within the NIU complex in Fe-S cluster reconstitution assays with DTT 11 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The first step crucially requires the cysteine desulphurase complex Nfs1-Isd11 (bacterial IscS; no Isd11 homologue known) that releases sulphur from cysteine by generating a Nfs1-bound persulphide (-SSH) intermediate 19 . Frataxin (yeast Yfh1) is crucial for mitochondrial Fe/S protein biogenesis, and has been proposed to serve as an iron donor and/or positive regulator of the desulphurase enzyme [20][21][22] . In Salmonella, a frataxin homologue also facilitates Fe/S protein assembly 23 , yet the Escherichia coli frataxin homologue CyaY inhibits Fe/S cluster synthesis in vitro and was suggested to be a negative regulator 24 .…”
mentioning
confidence: 99%
“…Additional studies demonstrated similar bacterial and yeast heterotetramers in which a dimer of IscS/ Nfs1 binds to one IscU/Isu1 monomer at each end, and it was further proposed that one CyaY/Yfh1 monomer could bind in a pocket between the cysteine desulfurase and the scaffold (10, 16 -18). Models based on these structures have also been pro-posed for the human proteins (19,20 (10,17). The mechanism of sulfur transfer to each of these sites is thought to involve a flexible loop of Nfs1 containing the invariant cysteine residue Cys-421, which becomes persulfurated at the end of the cysteine desulfurase reaction (12).…”
mentioning
confidence: 99%